The Influence of Teachers' Educational Background on Interest in Learning Social Science - Ganda Marito Harahap; Diana Eka Pratiwi; Fadhilah Yunus; Aroiz Azhari Rambe; Rizki Fahmi; Eka Yusnaldi (Pusdikra-Publishing.com, 2024)
This research aims to examine the influence of teacher educational background on students' interest in learning Social Sciences (IPS) based on a literature review. This literature study collects and analyzes various relevant journals to understand how teacher education and training can influence students' motivation and interest in learning in social studies subjects. Literature analysis shows that teachers with higher educational qualifications and adequate professional training tend to be able to create a more effective and interesting learning atmosphere, thereby increasing students' interest in learning. This research found that factors such as teacher education level, teaching experience, and participation in professional development programs have a significant effect on students' interest in learning. This study also identified that innovative and interactive teaching methods applied by highly educated teachers can motivate students to be more active in learning social studies. Recommendations from this study emphasize the importance of improving qualifications and continuous training for teachers to improve the quality of education and students' interest in learning. This research makes an important contribution to the field of education by providing insight into how a teacher's educational background can influence students' learning interest in social studies subjects.